Komik Pendidikan sebagai Media Inofatif MI/SD - Sigit Dwi Laksana (Ta'allum: Jurnal Pendidikan Islam, 2015)
As a teaching media, a picture in a comic means thousand words. Edward Lee Thorndike conducts a research on the benefit of using comic for learning and the results shows that using comic is effective in improving learners’ mastery of vocabulary. As a teaching media, educational comics which are specially designed for educational purpose are effective to help low motivated learners.